Interpreting mosaicism in chorionic villi: results of a monocentric series of 1001 mosaics in chorionic villi with follow‐up amniocentesis. (11th September 2015) - Malvestiti, Francesca; Agrati, Cristina; Grimi, Beatrice; Pompilii, Eva; Izzi, Claudia; Martinoni, Lorenza; Gaetani, Elisa; Liuti, Maria Rosaria; Trotta, Anna; Maggi, Federico; Simoni, Giuseppe; Grati, Francesca Romana
Abstract: Objectives: Chromosomal mosaicism in chorionic villi (CV) is detected in 1–2% of cases. When a mosaic in CV is detected during prenatal diagnosis, a confirmatory karyotype should be performed on amniocytes to discriminate between a mosaic confined to the placenta [confined placental mosaicism (CPM)] and one generalized to the fetus [true fetal mosaicism (TFM)]. We determined the likelihood that any mosaic abnormalities identified through CV samples are confirmed in the fetus. Methods: Over a period of 14 years, the laboratory analyzed both the cytotrophoblast and the mesenchyme of 60 347 CV samples. Cytogenetic results from CV samples showing mosaicism with follow‐up amniocentesis were considered. The incidence of CPM and TFM and the risk of confirmation in the amniotic fluid (AF) were calculated. Uniparental disomy (UPD) was tested on 300 cases at risk due to involvement of an imprinted chromosome. Results: Overall, 1317 mosaic CV cases (2.18%) were detected, of which 1001 were subsequently investigated by amniocentesis. The overall risk of TFM was 13% and UPD incidence was 2.1%. Conclusions: The very large presented sample set and consistency in cytogenetic methodology, especially the analysis of both placental layers performed on all CV samples will enable genetic counselors to determine the risk of fetal involvement and the clinical relevance of an identified mosaic condition. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Chromosomal mosaicism in chorionic villi (CV) is detected in 1–2% of cases, and the distribution of normal and abnormal cell lines in the fetus and placenta depends on the time and place of the mitotic event generating the mosaicism. Approximately 10% of CV mosaicism is confirmed in the fetus. What does this study add? We present the largest monocentric data set including 1001 consecutive chromosomal mosaicism detected on CV samples analyzing both placental layers and followed by confirmatory amniocentesis. We determined the likelihood that any mosaic chromosomal aberration (either numerical or structural) identified from a CV samples will be confirmed as evident in the fetus.